PENGARUH MODEL PEMBELAJARAN PACE TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS - Saputri, Rikhel; Warti, Rini; Murtadlo, Ali (Math Educa Journal, 2023)
This research is a quantitative study using One-Group Pretest-Posttest Design design while collection of data using test technique. Sample in this research is student of semester IV in Mathematics Education Program as much 25 students who mathematical creative thinking ability low. Researchers found that students mathematical creative thinking ability after applying PACE learning model is better than students mathematical creative thinking before applying PACE learning model. The result of the analysis shows that there is a significant difference between students mathematical creative thinking ability before applying PACE learning model and after applying PACE learning model on Opportunity material with t_count bigger than t_table, both in level of significance 5% and 1%, which it 2,06 4,90 2,80. The results of the research is suggest that lecturers to applying PACE learning model in teaching Mathematics Statistics study.